Otolaryngology consultations requested by palliative care services: a five-year analysis - Yasemin Kurtoğlu; Mehmet Varol; Nurullah Türe (SERNEV, 2023)
Introduction: Otolaryngologists are required to possess the knowledge, skills, and confidence necessary to manage consultations requested by palliative care services. However, the inclusion of palliative care needs in otolaryngology residency training is limited. The goal of this study was to enhance awareness of otolaryngologists' palliative care knowledge and skills by evaluating otolaryngology consultations requested by tertiary palliative care services between 2016 and 2021.Methods: This retrospective cross-sectional study included patients who consulted the otolaryngology department from the palliative care service of Kutahya Health Sciences University between January 1, 2016 and September 31, 2021. A total of 80 otolaryngology consultations were requested between 2016 and 2021. Patients were evaluated for age, gender, diagnosis of palliative admission, reason for consultation, date of consultation, interventions, and additional investigations.Results: There were 27 female patients (33.7%) and 53 male patients (66.2%). The mean age was 65.0 (range: 22-97) years. It was found that the volume of consultations did not increase significantly over a five-year period (p=0.502) and 78.8 % of consultations were requested during working hours (08:00-16:00). In addition, the response time (minutes) for consultations during working hours (08:00-16:00) was significantly lower than outside working hours (16:01-07:59) (p lt;0.001). The reasons for requesting a consultation and the procedures performed were significantly different between patients under and over 65 years of age (p=0.019 and p=0.008, respectively).Conclusions: This is the first study to evaluate otolaryngology consultations requested by a tertiary palliative care service. Awareness of these consultations may provide guidance for the assessment and management of patients in palliative care services.Keywords: consultation, otolaryngology, tracheotomy, palliative care